1977
DOI: 10.1063/1.435342
|View full text |Cite
|
Sign up to set email alerts
|

M dependence of T1 and T2 for the inversion doublets of 15NH3

Abstract: The pressure dependence of T1 and T2 has been measured for the ΔM=0, ‖M‖ inversion transitions in the (J=2,K=2) and (J=3,K=3) rotational states of 15NH3. We find the T2 is not M dependent but that T1 is strongly M dependent. These results are successfully interpreted by using a modified version of the Anderson impact theory which shows an M2 contribution to T1. The consequences of these results to other experiments are also considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…It is important to note that each level is (2 J + 1)-fold degenerate with the quantum number M J and that rates in this work are in fact average rates in contrast to the Stark-switching-type experiments where individual | M J | states are resolved. The M dependency of T 1 as discussed by Hoke et al 10 explains their significantly higher value of T 1 –1 compared to our and Amano’s work. In addition, our T 2 –1 contains also contributions from reorientation collisions (only Δ M J ≠ 0).…”
supporting
confidence: 57%
See 1 more Smart Citation
“…It is important to note that each level is (2 J + 1)-fold degenerate with the quantum number M J and that rates in this work are in fact average rates in contrast to the Stark-switching-type experiments where individual | M J | states are resolved. The M dependency of T 1 as discussed by Hoke et al 10 explains their significantly higher value of T 1 –1 compared to our and Amano’s work. In addition, our T 2 –1 contains also contributions from reorientation collisions (only Δ M J ≠ 0).…”
supporting
confidence: 57%
“…4 Additional time-resolved measurements based on Stark-switching techniques enabled direct observations of rotational relaxation in ammonia, including its M dependence, and the application of double-resonance techniques in a beam-maser chamber allowed Kukolich, 5 and later Klaassen et al, 58 to measure scattering cross sections and compare their experimental values with ones calculated using a modified version of Anderson’s theory. 9,10 The comparison of experimentally derived pressure-broadening and pressure-shift parameters obtained from an observation of the line shapes with those predicted by theory has been the most commonly used technique to study collisions to date. Since the early work of Bleaney and Penrose, 1113 the line shapes of ammonia have been studied extensively at microwave and infrared frequencies with a number of different collision partners.…”
mentioning
confidence: 99%
“…In case of the N H 3 system it has been found that the values of TJT2 lie between 1 and 2 for different inversion lines [3][4][5]. This behav iour is due to the fact that collisions of type (ii) are also important, besides collisions of type (iii), as has been successfully explained using a perturbative approach to collision dynamics [5][6][7], For some systems the values of \/Tl have been reported to be slightly smaller than the corresponding values of 1/T2 [8]. However, there was no system known previous to this work for which the value of 1/Ti is considerably smaller than the corresponding value of 1/T2.…”
Section: Introductionmentioning
confidence: 99%